AGNIHOTRA EFFECT ON MICROBIAL CONTAMINATION OF AIR - KUMARI RICHA,; PUNAM,; PANDA A. K.,; ATUL, (The Bioscan, 2015)
In the present study, the effect of agnihotra practices was observed on the microbiological quality of air in an organic environment at Palampur. Air quality of Agnihotra and Non – Agnihotra rooms were compared by collecting samples at three different time interval viz. half an hour before, at the time of agnihotra and half an hour after agnihotra using Settle Plate Method and blood agar as medium. It was observed that the total number of mesophilic colony units per plate (cfu/plate) was higher (70 cfu) in non - agnihotra room as compared to agnihotra room (23 cfu). The average thermophillic count per plate was also found to be 3 cfu in non - agnihotra room whereas, it was not detected in agnihotra room. The present findings indicate that the agnihotra practices have an adverse effect on the pathogenic micro-organisms (especially on those growing at higher temperature) and total microbial load of the air.